The 2015 Wolf volcano (Galápagos) eruption studied using Sentinel‐1 and ALOS‐2 data. Issue 18 (28th September 2016) - Xu, Wenbin; Jónsson, Sigurjón; Ruch, Joël; Aoki, Yosuke
Abstract: An energetic eruption started on 25 May 2015 from a circumferential fissure at the summit of Wolf volcano on Isabela Island, western Galápagos. Further eruptive activity within the Wolf caldera followed in mid‐June 2015. As no geodetic observations of earlier eruptions at Wolf exist, this eruption provides an opportunity to study the volcano's magmatic plumbing system for the first time. Here we use interferometric synthetic aperture radar (InSAR) data from both the Sentinel‐1A and ALOS‐2 satellites to map and analyze the surface deformation at four time periods during the activity. These data allow us to identify the two eruption phases and reveal strong coeruptive subsidence within the Wolf caldera that is superimposed on a larger volcano‐wide subsidence signal. Modeling of the surface displacements shows that two shallow magma reservoirs located under Wolf at ~1 km and ~5 km below sea level explain the subsidence and that these reservoirs appear to be hydraulically connected. We also suggest that the transition from the circumferential to the intracaldera eruption may have involved ring fault activity. Key Points: The 2015 Wolf volcano (Galápagos) eruption studied using both Sentinel‐1A and ALOS‐2 satellite radar data Coeruption deformation explained with two magma reservoirs at 1 km and 5 km depths below sea level that may be hydraulically connected Observed ground deformation may have been influenced by ring fault activity